Peran Transnational Social Movement Black Lives Matter dalam Mewujudkan Kesetaraan Rasial TerhadapKelompok Minoritas Kulit Hitam di Inggris Raya Tahun 2020 - 2021 - Sultan Muhammad Fadhil, (2022)
This research will talk about the role of transnational Black Lives Matter in the movement to realize racism against minority groups in the United Kingdom in 2020-2021. This study will use the concept of institutional racism and transnational social movements as an analytical knife. The methodological approach that will be used is a case study qualitative method. This study found that the existence of institutional racism at the individual, intra-organizational, and intra-organizational levels occurred in the United Kingdom. Institutional racism occurs in many aspects of black people's lives such as education, economy, health, and law. There has been an increase in racism during the covid-19 pandemic that black people have faced. This research also uncovers the role and contribution of the transnational Black Lives Matter movement as a racial promoter in the United Kingdom. Contribution through helping narratives of racism at the local level to be able to rise to the international level, as well as putting pressure on policy makers through campaigns on social media and demonstrations.